Precision therapy, beautiful tomorrow - Kumada, Hiroaki; Chen, Yi-Wei (Therapeutic Radiology and Oncology, 2018)
Cancer treatment has been advancing rapidly, with continuous breakthroughs in new radiotherapy techniques. Although many new radiotherapy machines develop after the twenty-first century, cancer control has no significant improvement by photon source’s limitation. Therefore, radiation therapy with high radiobiological effectiveness is required extremely.